2016
DOI: 10.1118/1.4961403
|View full text |Cite
|
Sign up to set email alerts
|

A particle filter based autocontouring algorithm for lung tumor tracking using dynamic magnetic resonance imaging

Abstract: This work presents a proof of concept of a new autocontouring algorithm for NSCLC patients on dynamic MR images. The contours were generated in good agreement with the expert's contours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
0
20
1
Order By: Relevance
“…It is unfeasible for a human expert to continually contour images at a rate of lower than 0.5 s per image for the duration of treatment. To address this, our group and others have previously proposed real time autocontouring algorithms. A key feature to imaging and contouring in real time is that it does not rely on regular, predictable motion of lung tumor.…”
Section: Introductionmentioning
confidence: 99%
“…It is unfeasible for a human expert to continually contour images at a rate of lower than 0.5 s per image for the duration of treatment. To address this, our group and others have previously proposed real time autocontouring algorithms. A key feature to imaging and contouring in real time is that it does not rely on regular, predictable motion of lung tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The most straightforward approach is to derive the position information directly from the MR image. Often used in this case is autocontouring, in which the tumor or organ is automatically delineated [202][203][204][205][206][207][208][209][210]. Alternative methods include template matching, in which a template shape, for example of an organ or tumor, is located on the dynamic MR images [175,177,211,212], artificial neural networks [175,178] and nonrigid image registration [157].…”
Section: Tracking and Motion Modelingmentioning
confidence: 99%
“…Several groups have shown that it is feasible to localise lung tumours in these images using template matching [144,97,145]. More advanced algorithms deploy artificial neural networks [144,146], scale-invariant feature transforms [147,148], or particle filtering [149] to quickly delineate the tumour in each image. The orientation of these 2D imaging planes with respect to the tumour motion can be freely set and even altered during image acquisition.…”
Section: Intrafractional Motion Managementmentioning
confidence: 99%